CEO INSIDER FROM CFO: IMPLICATIONS FOR FINANCIAL RISK DISCLOSURE QUALITY - Ningsih, Sri; Mujtaba, Muhammad Irsyad Elfin; Oehoedoe, Muhammad Sabrian; Aini, Siti Nur (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: Financial risk disclosure is crucial due to the broad-ranging consequences that may arise from inadequate disclosure, with the role and capabilities of a company's top management being essential in addressing this issue. This study examines the impact of CEO insiders with prior experience as CFOs on the quality of financial risk disclosure (FRDQ) in Indonesia. Methods: Using OLS regression analysis, the study analyzes data from non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2010 to 2020. To enhance the reliability of the results, robustness tests are conducted using the Heckman Two-Stage model and Coarsened Exact Matching (CEM). Findings: The findings indicate that CEOs who previously served as CFOs within the same company contribute to improved FRDQ. Additionally, several sub-sample analyses were included to explore other supporting factors in strengthening FRDQ. Conclusion: This study concludes that a CFO background provides a deeper understanding of the company's financial condition, thereby enhancing financial risk disclosure. Novelty/Originality of this article: The study specifically investigates the impact of CEO insiders with CFO backgrounds on financial risk disclosure quality in the Indonesian context.